Comparative Numerical Aerodynamics Performance Analysis of NACA0015 and NACA4415 Airfoils - Kepekci, Haydar (Malikussaleh University, Aceh, Indonesia, 2022)
The climate crisis caused by global greenhouse gas emissions has led to many disasters around the world in recent years. Some of these disasters are floods in various parts of Europe, melting of Arctic glaciers, and rising water levels in the oceans. People living on islands in Southeast Asian countries are forced to migrate due to rising water levels. With the increase in the frequency of such situations, life on earth is at risk. Greenhouse gas emissions harm not only humans but also animals and plants. The most effective measure that can be taken against this is to stay away from fossil fuels. With the use of fossil fuels, the carbon ratio in the atmosphere increases, and climatic imbalances occur. For this reason, the interest in alternative energy sources is increasing. Wind energy is one of the most widely used renewable energy sources. This is due to the low cost of installation and ease of use. The most important factor affecting the aerodynamic efficiency of wind turbines is the blade profiles. Numerous types of wing profiles have been designed and put into use. In this study, numerical analyzes of NACA 0015 and NACA 4415 airfoils at various angles of attack were performed by determining forces every five degrees between 0 and 20 degrees using ANSYS Fluent commercial software. Lift coefficients and drag coefficients were also calculated for the angles of attack used. According to the analysis results obtained, optimum attack angles were found for each airfoil. As a result, NACA0015 and NACA4415 airfoils were compared in terms of their performance.